Bone mineral density: Comparison between women under hormone replacement therapy with Turner syndrome or idiopathic premature ovarian insufficiency - Nelis, Charlotte; Belin, Lisa; Tejedor, Isabelle; Dulon, Jerome; Bachelot, Anne; Chakhtoura, Zeina (Annales d'endocrinologie, 2024)
•At first evaluation under HRT, lumbar and femoral neck BMD were poorer in the Turner syndrome (TS) than in the idiopathic premature ovarian insufficiency (POI) group.•Mosaic karyotype was associated with better BMD in TS patients while growth hormone treatment had no impact on BMD.•Over time, on HRT, a significant gain in vertebral BMD was observed in patients with TS, compared with a loss of BMD in patients with idiopathic POI. Turner syndrome (TS) is characterized by short stature and premature ovarian insufficiency (POI). The main long-term complication of POI is osteoporosis, which can be prevented by hormone replacement therapy (HRT). The objective of our study was to compare initial bone mineral density (BMD) and progression between TS and idiopathic POI patients under HRT. A single-center retrospective study was conducted between 1998 and 2018. All women had undergone at least two bone densitometry assessments at least 2 years apart. Sixty-eight TS patients and 67 idiopathic POI patients were included. Mean age at initial assessment was 27 years (IQR, 21–35.5 years) in TS patients and 31.5 years (IQR, 23–37 years) in idiopathic POI patients (P=0.1). Lumbar and femoral neck BMD were lower in the TS group than in the idiopathic POI group (respectively 0.89g/cm2 versus 0.95g/cm2, P=0.03; 0.70g/cm2 versus 0.77g/cm2, P<0.0001). Mosaic karyotype was associated with better BMD in TS patients while history of growth hormone treatment had no impact on BMD. Over time, a significant gain in vertebral BMD was observed in TS patients versus a loss of BMD in idiopathic POI patients (P=0.0009). TS patients had a lower BMD at baseline than idiopathic POI patients, at both spinal and femoral levels. Over time, on HRT, a significant gain in vertebral BMD was observed in patients with TS, compared with a loss of BMD in patients with idiopathic POI. We hypothesized that earlier initiation and longer duration of HRT played an important role in this finding. Long-term prospective follow-up to assess the incidence of fractures in TS would be useful.